2018
DOI: 10.1158/1078-0432.ccr-17-1628
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Function-Blocking Antibody Against Fibulin-3 as a Targeted Reagent for Glioblastoma

Abstract: We sought a novel approach against glioblastomas (GBM) focused on targeting signaling molecules localized in the tumor extracellular matrix (ECM). We investigated fibulin-3, a glycoprotein that forms the ECM scaffold of GBMs and promotes tumor progression by driving Notch and NFκB signaling. We used deletion constructs to identify a key signaling motif of fibulin-3. An mAb (mAb428.2) was generated against this epitope and extensively validated for specific detection of human fibulin-3. mAb428.2 was tested in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Fibulin-3, an extracellular matrix glycoprotein, is highly expressed in Glioblastoma and functions as an autocrine/paracrine activator of NF-κB and the Notch pathway, promoting tumor invasion, angiogenesis, and drug resistance, besides being a marker of poor prognosis [167]. Nandhu et al developed an antibody against fibulin-3 called mAb428.2, which is able to prevent the fibulin-3-activation of ADAM17, resulting in cell apoptosis, enhancement of inflammatory macrophage infiltration, reduced tumor growth and vascularization, and extended survival in Glioblastoma mouse models [167]. Always with regard to fibulin-3, Li et al developed ZR30, an in vitro synthetized protein, based on the human fibulin-3 protein variant (ETSP), lacking the N-terminal signal peptide (responsible for extracellular exportation).…”
Section: Notch Signaling and Glioblastomamentioning
confidence: 99%
“…Fibulin-3, an extracellular matrix glycoprotein, is highly expressed in Glioblastoma and functions as an autocrine/paracrine activator of NF-κB and the Notch pathway, promoting tumor invasion, angiogenesis, and drug resistance, besides being a marker of poor prognosis [167]. Nandhu et al developed an antibody against fibulin-3 called mAb428.2, which is able to prevent the fibulin-3-activation of ADAM17, resulting in cell apoptosis, enhancement of inflammatory macrophage infiltration, reduced tumor growth and vascularization, and extended survival in Glioblastoma mouse models [167]. Always with regard to fibulin-3, Li et al developed ZR30, an in vitro synthetized protein, based on the human fibulin-3 protein variant (ETSP), lacking the N-terminal signal peptide (responsible for extracellular exportation).…”
Section: Notch Signaling and Glioblastomamentioning
confidence: 99%
“…It suppresses tumor cell proliferation, migration, and invasion through inhibition of the MAPK and AKT pathways and regulation of cell adhesion molecules as well as ECM-associated genes and miRNAs. Anti-adhesion has evolved to a promising therapeutic concept in oncology [ 64 ], and recently, an “anti-ECM” strategy using a function-blocking antibody against Fibulin 3 has been proved in treatment of murine glioblastoma [ 65 ]. The cancer growth inhibitory role of FBLN2, as revealed in this study, may provide a basis for further exploring its therapeutic value in human lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many oncogenes, anti-oncogenes and pathways participate in the tumorigenesis process and metastasis. FBLN3, which is also called epidermal growth factor-containing fibulin-like extracellular matrix protein 1 (EFEMP1), is related to many diseases, such as age-related macular degeneration [7], knee osteoarthritis [8], asbestos-related diseases [9], rheumatoid arthritis [10], mesothelioma [11], glioblastoma [12], osteosarcoma [13], ovarian cancer [14] and cervical cancer [15]. Many studies have reported that the fibulin family, which consists of 7 secreted extracellular glycoproteins, is involved in cell morphology maintenance, cell growth, adhesion and movement.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results indicate that FBLN3 may act as an anti-oncogene in CRC. FBLN3 can also have anti-cancer effects and be a therapeutic target in malignant tumors [26,27].…”
Section: Discussionmentioning
confidence: 99%